Consumed in China: Rebalancing China's demand and Chinese imports - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
The share of private consumption has long been small in the Chinese GDP. The share started to increase in the past decade, but the trend reversed with the covid-19 pandemic. Now as the Chinese economy reopens and recovers from covid restrictions, the share of consumption could return to a growing trend. This resumption of a longer-term trend could have important implications for global trade. Our simulations, which are based on recent international input-output data, suggest that the current shift in China's demand structure is likely to increase import demand for sectors such as the food industry, agriculture, textiles, and travel services. Sectors facing a demand slowdown include base metals, non-metallic minerals, and machinery and equipment.
urn:nbn:fi-fe2023031431511
Keywords: 330; China; imports; rebalancing; input-output